Directive Speech Acts in Different Social Classes - Dwi Indarti (Wanastra: Jurnal Bahasa dan Sastra, 2019)
This paper tries to investigate the use of directive speech acts in different social class. Using the six types of directive speech acts proposed by Ervin-Tripp (1976), which are need statement, imperative, imbedded imperative, permission directive, question directive and hint, this paper focuses on the main male characters’ utterances from two novels; Crazy Rich Asians written by Kevin Kwan which represents upper class society and I am the Messenger written by Markus Zusak which represents lower class society. The results show that both upper and lower social classes mostly use imperative directive (42 utterances or 80%). Lower class male character uses more ‘need statement directive’ than upper class male character. Meanwhile, upper class character uses more ‘question directive’ than lower class character. Generally, upper class people use the directive as commands to their employees while the lower class character uses directive in his work as a cab driver which required him to be more direct in asking and offering the customers